An item analysis on multiple-choice questions: a case of a junior high school English try-out test in Indonesia - Rohmatul Jannah; Didin Nuruddin Hidayat; Nida Husna; Imam Khasbani (University of Muhammadiyah Purwokerto, 2021)
The present study aims to analyze multiple-choice questions obtained from a trial testing conducted in a state junior high school in Indonesia. The study seeks to reveal the level of difficulty, discriminating power and distractor efficiency of the selected test items by employing item analysis. The result of the study discovers that levels of difficulty on the question items are varied. Some question tended to be easy and moderately difficult while the others are difficult to answer. It also uncovers that, in regard to discriminating power, some questions are well constructed while the others are ambiguously worded that can potentially cause the questions to fail to evaluate the students’ ability. The analysis on distractor efficiency presents information how the chosen multiple-choice questions were frequently constructed with less effective distractors that caused more high achieving students to choose wrong answers.